Prevalence of bovine mastitis pathogens and antibioresistance of Escherichia coli isolates - ZDRAGAS (Α. ΖΔΡΑΓΚΑΣ), A.; TSAKOS (Π. ΤΣΑΚΟΣ), P.; ANATOLIOTIS (Κ. ΑΝΑΤΟΛΙΩΤΗΣ), K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Nine hundred and fifty two milk samples from clinical bovine mastitis cases, originated from 269 farms in Northern Greece, were tested. Escherichia coli was isolated in 49.3% of samples. Furthermore, Staphylococcus spp, Corynebacterium spp, Streptococcus spp, Pseudomonas spp, Proteus spp, Klebsiella spp or a combination of the above bacteria were isolated. The bacteriological result from 4.3% of samples was negative. No correlation between clinical mastitis cases and seasonal variation was observed. Resistance of E. coli isolates to tetracycline was 82-96%, to enrofloxacin 10-30%, to gentamicin 58-80%, to cephalosporins 47-75%, to sulfamethoxazole-trimethoprime 46-81%, to ampicillin 71-92% and to neomycin 83-97%. The highest resistance rate and the appearance of multi-resistant isolates of E. coli (6%), to 8 antibacterials, were recorded during the last year of the survey.